2019
DOI: 10.1111/jfd.13096
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the microbial communities in the gastrointestinal tract of perch (Perca fluviatilis L. 1758) and cestodes parasitizing the perch digestive tract

Abstract: Using the approach of sequencing the V3‐V4 region of the 16S rRNA gene, we have analysed the bacterial diversity associated with the distinct compartments of the gastrointestinal tract of perch (Perca fluviatilis) and cestodes (Proteocephalus sp.) parasitizing their digestive tract. The dominant microbiota associated with cestodes (Proteocephalus sp.) was represented by bacteria from the genera Serratia, Pseudomonas and Mycoplasma. By comparing the associated microbiota of perch and cestodes, a clear differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…Following the kit manufacturer protocols, DNA was extracted using the DNA-sorb B kit (NextBio, Russia). The DNA extraction protocol was previously described in Kashinskaya et al (2020) . DNA from a sample containing only sterile deionized water was extracted and included in PCR as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the kit manufacturer protocols, DNA was extracted using the DNA-sorb B kit (NextBio, Russia). The DNA extraction protocol was previously described in Kashinskaya et al (2020) . DNA from a sample containing only sterile deionized water was extracted and included in PCR as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Interactions between bacterial diversity found in the host and the microbes associated with the helminthes have been studied less extensively in fish. To date, it has been shown that different ecto- and endoparasites of fish are known to harbor a unique bacterial community ( Hughes-Stamm et al, 1999 ; Poddubnaya and Izvekova, 2005 ; Korneva and Plotnikov, 2006 ; Llewellyn et al, 2017 ; Gonçalves et al, 2020 ; Kashinskaya et al, 2020, 2021 ). In particular, a bacterial species was found to colonize the different areas of cestode teguments of Trianophorous nodulosus, Eubothrium rugosum and Ligula intestinalis from the intestine of pike, burbot, and bream, correspondingly ( Izvekova and Lapteva, 2004 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA extraction protocol was previously described in Kashinskaya et al . (2020). DNA from a sample containing only sterile deionized water was extracted and included in PCR as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…In present study, high starch diet feeding resulted in increasing relative abundance of Mycoplasmas, and there was a positively correlation was observed between relative abundance of mycoplasma with in ammatory(TNF-α, IL-1β, IL-8 and hepcidin1,2) and apoptotic(caspase-3,8,9 and bax) genes. Carbohydrates are the main source of energy for mycoplasma and converted to lactic acid and acetic acid, which are essential for immune and in ammation regulation (Brown, 2002;Kashinskaya et al, 2019). Furthermore, host immune system also plays a key role in shaping gut microbial communities (Kokou et al, 2019).…”
Section: High-starch Diet Impaired Intestinal Microbial Barriermentioning
confidence: 99%